2014
DOI: 10.1186/s12967-014-0296-9
|View full text |Cite
|
Sign up to set email alerts
|

Graphene based scaffolds effects on stem cells commitment

Abstract: Graphene is a flat monolayer of carbon atoms, arranged in a two-dimensional hexagonal structure, with extraordinary electrical, thermal, and physical properties. Moreover, the molecular structure of graphene can be chemically modified with molecules of interest to promote the development of high-performance devices. Although carbon derivatives have been extensively employed in industry and electronics, their use in regenerative medicine is still in an early phase. Study prove that graphene is highly biocompati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
80
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(91 citation statements)
references
References 50 publications
2
80
0
3
Order By: Relevance
“…The remarkable effects of graphene in osteogenic differentiation of stem cells support its introduction as an alternative material for bone regeneration [3][4][5][6]9,[11][12][13][14][15]. Graphene-based materials can accelerate the differentiation towards osteoblast-like cells [3][4][5][6].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The remarkable effects of graphene in osteogenic differentiation of stem cells support its introduction as an alternative material for bone regeneration [3][4][5][6]9,[11][12][13][14][15]. Graphene-based materials can accelerate the differentiation towards osteoblast-like cells [3][4][5][6].…”
Section: Introductionmentioning
confidence: 98%
“…The material is capable to maintain induced pluripotent stem cells (iPSC) in the http://dx.doi.org/10.1016/j.carbon.2015.05.071 0008-6223/Ó 2015 Elsevier Ltd. All rights reserved. undifferentiated state [7] and also to induce stem cell differentiation into specific lineages [9]. Substrates coated with graphene-based materials are capable to promote the differentiation of human embryonic stem cells into cardiomyogenic cells [10] and to enhance differentiation of human neural stem cells into neurons [8].…”
Section: Introductionmentioning
confidence: 99%
“…Graphene and its derivatives were used as nanoplatforms for promoting cell proliferation, cell adhesion, and differentiation of various embryonic stem cells (ESCs). 45 Although several studies showed the biocompatibility of graphene using different biological models, only few studies reported the biocompatibility of rGO-assisted biomolecules in MEFs to date. In this study, we explored a novel biological molecule called nicotinamide (NAM), a water-soluble amide form of niacin (vitamin B3) involved in energy metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have proved the ability of GO to promote stem cell differentiation into osteogenic, cardio, neuronal, and adipogenic lineages. [140][141][142][143] Of particular note is the recent work by Kim et al 33 in which a novel strategy to guide stem cell differentiation into specific cell lineages by employing combinatorial GO hybrid-patterns of specific geometries was reported. NGO combinatorial pattern-arrays, with different sizes and geometries, were successfully transferred to various substrates such as Au-coated glass, molded polystyrene, flexible polydimethylsiloxane, and even biodegradable poly(lactic-coglycolic acid) film.…”
Section: Tissue Engineeringmentioning
confidence: 99%